CHARACTER PROBLEM IN KAZAT AKMATOV'S STORIES - Тоlubaeva Ch. D.; Nurkulova N.; Dootalieva М. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article analyzes the stories of the writer Kazat Akmatov “Olesya, Alisa” and “Today’s cinema is not about war”, and examines the artistry of the works. Also, the theme of war in the author’s stories is analyzed through the images of the heroes, the author’s skill in creating a plot and characterizing the characters is determined. In addition, the author's article analyzes the fact that through the fate of ordinary people, the suffering of the entire human race from war will be reflected for centuries, and that peace and freedom are the most important things, no matter what kind of life a person lives. At the same time, the image of a mother who has lost her child, living with unbroken hope and hope that news will come from the future, is analyzed.